Desenvolvimento de espumas vítreas para aplicação como fotocatalisador de corante têxtil. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
The final disposal of solid waste has gained more and more importance, whether due to the environmental and/or economic appeal, among these materials, glass and batteries stand out. In this work, waste of flat glass and spent alkaline batteries were used as raw materials in the production of foam glass, aiming at their use in the degradation of textile dyes through Advanced Oxidative Processes (AOPs). The foam glass obtained were characterized by field emission scanning electron microscopy (SEM-FEG), X-ray diffractometry (XRD), volumetric expansion, apparent porosity and density, diffuse reflectance, adsorption and degradation efficiency were calculated using as target molecule the methylene blue dye, quantified by spectrophotometry in the visible region (UV-Vis). The XRD results of the anode and cathode of spent batteries demonstrated components and the presence of the phases of compounds that can act as foaming agents in obtaining foam glass, highlighting the environmental character of this work, since these residues can replace commercial foaming agents. The physical analysis of the batteries showed densities that ranged from 0.4 g cm-3 to 0.8 g cm-3 of the samples obtained with alkaline batteries, in addition to an apparent porosity of up to 64%. The adsorption tests using the foam glass with the presence of both the anode and cathode of the batteries showed a removal of about 10% of the dye and showed a degradation efficiency of up to 95%, after 3 hours of exposure to a LED lamp with 15W power. The DOE showed that, with the parameters established, there is no significant effect on the power of the lamp used, nor on the pH of the solution, which allows the use of lamps of lower power and the use of their pH without alteration, only being the presence of H2O2 is required. These results indicate the viability of using residues to obtain and use foam glass for photocatalysis.
Keywords: reciclagem; processos oxidativos avançados; cerâmica celular; catalisador heterogêneo; recycling; advanced oxidative processes; cellular ceramics; heterogeneous catalyst; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA